2017
DOI: 10.14503/thij-16-5879
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Sustained Ventricular Fibrillation During Continuous-Flow Left Ventricular Assist Device Support

Abstract: The widespread use of continuous-flow left ventricular assist devices for mechanical circulatory support has shown that long-term hemodynamic support is possible, even when a clinical “pulse” cannot be detected. We present the incidental discovery of ventricular fibrillation in 6 alert, hemodynamically stable patients supported only by a continuous-flow device (HeartMate II, n=5; Jarvik 2000, n=1). Ventricular fibrillation was found in 3 patients during routine outpatient follow-up visits and in 3 awaiting dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The burden of VA in LT-MCS recipients is high; preoperative VA is the major predictor of late postoperative VA. VA is reasonably tolerated by many patients supported by LT-MCS with a low risk of immediate haemodynamic collapse [436]. The role of implantable cardioverter defibrillators (ICDs) for primary prevention of sudden cardiac death is unclear in patients supported by LT-MCS [84, 437].…”
Section: Pump Thrombosis and Other Late Adverse Eventsmentioning
confidence: 99%
“…The burden of VA in LT-MCS recipients is high; preoperative VA is the major predictor of late postoperative VA. VA is reasonably tolerated by many patients supported by LT-MCS with a low risk of immediate haemodynamic collapse [436]. The role of implantable cardioverter defibrillators (ICDs) for primary prevention of sudden cardiac death is unclear in patients supported by LT-MCS [84, 437].…”
Section: Pump Thrombosis and Other Late Adverse Eventsmentioning
confidence: 99%
“…11,12 However, as seen in our case, it is very important to defibrillate even asymptomatic patients with ongoing VAs to sinus (or paced) rhythm as soon as possible, since their ability to maintain adequate hemodynamic stability remains tenuous and can lead to right ventricular failure due to prolonged dysrhythmia. 17 Noteworthy in our case was the presence of organized contractility and rhythmic opening of the mitral valve on echocardiogram despite ventricular fibrillation on ECG. While some cardiac motion and valve opening could be explained by the negative pressure generated by the device, ventricular fibrillation is generally thought to manifest as asynchronous ventricular activity.…”
Section: Discussionmentioning
confidence: 59%
“…While patients were symptomatic, there was no evidence of end-organ dysfunction as a result of the ventricular arrhythmia. After restoration of sinus rhythm, there was no recurrence of the ventricular arrhythmia [42]. This suggests that there can be hemodynamic stability with left VAD support during episodes of ventricular arrhythmia.…”
Section: Management Of Arrhythmias Encountered In Patients With Ventr...mentioning
confidence: 73%
“…Studies have demonstrated that some adult patients with continuous-flow VAD remain hemodynamically stable while in ventricular tachyarrhythmia including ventricular fibrillation [40,[42][43][44]. While patients were symptomatic, there was no evidence of end-organ dysfunction as a result of the ventricular arrhythmia.…”
Section: Management Of Arrhythmias Encountered In Patients With Ventr...mentioning
confidence: 99%